A Mystery Unraveled: Non-tumorigenic pluripotent stem cells in human adult tissues - Simerman, Ariel A. (2014)
Embryonic stem cells and induced pluripotent stem cells have emerged as the gold standard of pluripotent stem cells and the class of 10 stem cell with the highest potential for contribution to regenerative and therapeutic application; however, their translational use is often impeded by teratoma formation, commonly associated with pluripotency. We discuss a population of nontumorigenic pluripotent stem cells, termed Multilineage Differentiating Stress Enduring (Muse) cells, which offer an innovative and 15 exciting avenue of exploration for the potential treatment of various human diseases. Areas covered: This review discusses the origin of Muse cells, describes in detail their various unique characteristics, and considers future avenues of their application and investigation with respect to what is currently known 20 of adult pluripotent stem cells in scientific literature. We begin by defining cell potency, then discussing both mesenchymal and various reported populations of pluripotent stem cells, and finally, delving into Muse cells and what sets them apart from their contemporaries. Expert opinion: Muse cells derived from adipose tissue (Muse-AT) are 25 efficiently, routinely and painlessly isolated from human lipoaspirate material, exhibit tripoblastic differentiation both spontaneously and under media-specific induction, and do not form teratomas. We describe qualities specific to Muse-ATcells and their potential impact on the field of regenerative medicine and cell therapy.